Disability and Extreme Poverty in Indonesia: Analysis of National Socio-Economic Survey Data in 2020 - Alabshar, Nufi; Pujiwati, Lina Agustina; Munawaroh, Titik; Fatoni, Zainal (Universitas Gadjah Mada, 2024)
Extreme poverty has become a global issue,and several studies indicate its relationship with disability. So far, there has been limited studies related to extreme poverty in Indonesia. Moreover, spesific segments, such as extreme poverty in persons with disabilities, are increasingly challenging to find. This study examines the effect of disability and other control variables on extreme poverty in Indonesia. The data is derived from the 2020 National Socio-Economic Survey (Susenas), which surveyed 1,258,328 individuals. The data was processed using STATA 17 software. The method used in this study is logistic regression by observing disability as the primary independent variable and other socio-demographic variables as control variables. Our analysis show that disability has a positive and significant relationship with extreme poverty. Control variables such as residence area, age group, sex, education, number of household members, marital status, and employment sector also play a role in influencing extreme individual poverty. These findings are expected to be able to enrich literature relatedto disability and extreme poverty in Indonesia as well as to provide input for the government in efforts to eradicate extreme poverty by paying attention to vulnerable groups,especially persons with disabilities.